2015
DOI: 10.1021/acs.jmedchem.5b01283
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Binding and Antiviral Properties of Potent Core-Extended Naphthalene Diimides Targeting the HIV-1 Long Terminal Repeat Promoter G-Quadruplexes

Abstract: We have previously reported that stabilization of the G-quadruplex structures in the HIV-1 long terminal repeat (LTR) promoter suppresses viral transcription. Here we sought to develop new G-quadruplex ligands to be exploited as antiviral compounds by enhancing binding toward the viral G-quadruplex structures. We synthesized naphthalene diimide derivatives with a lateral expansion of the aromatic core. The new compounds were able to bind/stabilize the G-quadruplex to a high extent, and some of them displayed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
124
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 93 publications
(124 citation statements)
references
References 70 publications
(141 reference statements)
0
124
0
Order By: Relevance
“…Indeed, the G4‐forming sequences appear to be highly conserved among subspecies thereby suggesting functional significance. For instance, independent studies have shown that derivatives of porphyrin, acridine, or naphthalene could interact with HIV‐G4 structures leading to the inhibition of key steps in the HIV‐1 viral cell cycle.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the G4‐forming sequences appear to be highly conserved among subspecies thereby suggesting functional significance. For instance, independent studies have shown that derivatives of porphyrin, acridine, or naphthalene could interact with HIV‐G4 structures leading to the inhibition of key steps in the HIV‐1 viral cell cycle.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the inherent different mechanism of action, G4 ligands could be envisaged as therapeutic options against HSV-1 strains resistant to current anti-herpetic drugs. In this direction, we have recently shown the availability of small molecules that target the HIV-1 G4s with a degree of selectivity vs the cellular telomeric G4s, resulting in very good antiviral properties (67). These data indicate the possibility to identify ligands selective for HSV-1 G4s.…”
Section: Discussionmentioning
confidence: 99%
“…We and other groups have identified functionally significant G4s in the Nef coding region16 and in the unique long terminal repeat (LTR) promoter171819 of HIV-1. When the HIV-1 G4s were stabilized by G4 ligands, antiviral effects, mainly dependent on inhibition of LTR-mediated transcription, were observed182021. Furthermore, the cellular protein nucleolin has been shown to stabilize the HIV-1 LTR G4s and induce potent inhibition of viral transcription22.…”
mentioning
confidence: 99%